Flora And Fauna Terms in Sundanese Sisindiran - Nonong Rowiyah; Yayat Sudaryat; Rahman (CV. Goresan Pena, 2023)
This paper aims to inventory and describe the lexicosemantic meaning of flora and fauna terms contained in Sundanese sisindiran. The methodology used in this paper is a qualitative approach and descriptive method. Data sources are taken from documents in the form of sisindiran books. To collect data, a literature study technique was used. The results presented as findings in this paper are an inventory of flora and fauna terms and their lexicosemantic meanings.